Airside thermal and hydraulic characteristics of compact bare tube heat exchanger under dry and wet conditions. (February 2020) - Huang, Zhiwei; Ling, Jiazhen; Bacellar, Daniel; Hwang, Yunho; Aute, Vikrant; Radermacher, Reinhard
Highlights: A compact bare tube heat exchanger was tested under both dry and wet condition. Discussed effect of inlet air relative humidity, air flow rate and water flow rate. Developed correlation for Chilton–Colburn j, jm and f correlations. Maximum variation of correlations is ±10%. Abstract: An experimental study was conducted to investigate the thermal and hydraulic performance of a compact bare tube heat exchanger, under both dry and wet condition. Chilton–Colburn j and f power law correlations were developed for Reynolds number range of 562–1266. Discrepancies between experimental data and new correlations are within ±2%. In wet mode, experimental conditions were varied by two inlet air humidity levels, three air flow rates and three water flow rates. From the experimental results, it was found that the heat transfer performance ( j factor) and friction ( f factor) decrease as air flow rate increases. Heat transfer performance decreases and friction increases slightly as inlet air humidity increases. But the changes are insensitive. Mass transfer ( jm factor) slightly decreases as air humidity increases. The effect of inlet air humidity, air flow rate and water flow rate on total heat transfer capacity, sensible heat, latent heat and pressure drop are discussed. Chilton–Colburn j, jm and f power law correlations were developed for Reynolds number range of 315–1080 under wet condition, with maximum deviation of ±10%, ±7% and ±7%.